Evaluation of the Effect of Chitosan-Based Irrigation Solutions on the Bond Strength of Mineral Trioxide Aggregate to Bulk-Fill Composite - Arzu Şahin Mantı; Bağdagül Helvacıoğlu Kıvanç (Journal of Functional Biomaterials)
(1) Background: Bond strength between repair and restorative materials is crucial for endodontic success. This study assessed the effects of the following final irrigation solutions on the bond strength of mineral trioxide aggregate (MTA) to a bulk-fill composite: (1) 17% Ethylenediamine tetraacetic acid (EDTA); (2) 2% Chlorhexidine (CHX); (3) 0.2% chitosan; (4) 0.2% chitosan with 2% CHX; 5) 0.2% chitosan with AgNPs. (2) Methods: Sixty MTA samples were divided into six groups (n = 10) based on the final irrigation solution: 1. EDTA, 2. CHX, 3. Chitosan, 4. Chitosan-CHX, 5. Chitosan-AgNP, and 6. distilled water (control). After a 5-min solution exposure, each sample was restored with the bulk-fill composite, and the shear bond strength (SBS) was measured. Structural changes in MTA were analyzed using SEM and EDS, and failure modes were classified as adhesive, cohesive, or mixed. Data were analyzed by one-way ANOVA with Tamhane’s T2 and Tukey’s tests (α = 0.05). (3) Results: EDTA exhibited the lowest SBS (p < 0.001), while Chitosan-CHX showed the highest. SEM showed a spongy, void-rich surface in EDTA-treated MTA, with significant Ca depletion per EDS. Chitosan-CHX showed no structural change. Cohesive fractures within MTA were predominant. (4) Conclusions: EDTA significantly reduces SBS, while chitosan with CHX enhances bond strength.